2021
DOI: 10.3389/fgene.2021.694009
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Immune-Related Long Non-coding RNA Prognostic Signature for Ovarian Cancer

Abstract: Ovarian cancer (OC), the most lethal gynecologic malignancy, ranks fifth in cancer deaths among women, largely because of late diagnosis. Recent studies suggest that the expression levels of immune-related long non-coding RNAs (lncRNAs) play a significant role in the prognosis of OC; however, the potential of immune-related lncRNAs as prognostic factors in OC remains unexplored. In this study, we aimed to identify a potential immune-related lncRNA prognostic signature for OC patients. We used RNA sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Among the top 10 lncRNAs found to be upregulated in vimentin‐positive IBC‐NSTs, although only LINC01694 and FAM74A7 have been reported previously as being significantly associated with a heightened malignant potential of carcinomas, 35,36 this study clearly demonstrated that the other eight lncRNAs could also be closely involved in accelerating the malignant potential of vimentin‐positive IBC‐NSTs; since there is as yet no published study report to suggest that these eight lncRNAs might also be closely associated with the outcome of carcinoma patients at the moment, these lncRNAs are most likely de novo lncRNAs accurately predicting the prognosis of patients with vimentin‐positive IBC‐NSTs.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Among the top 10 lncRNAs found to be upregulated in vimentin‐positive IBC‐NSTs, although only LINC01694 and FAM74A7 have been reported previously as being significantly associated with a heightened malignant potential of carcinomas, 35,36 this study clearly demonstrated that the other eight lncRNAs could also be closely involved in accelerating the malignant potential of vimentin‐positive IBC‐NSTs; since there is as yet no published study report to suggest that these eight lncRNAs might also be closely associated with the outcome of carcinoma patients at the moment, these lncRNAs are most likely de novo lncRNAs accurately predicting the prognosis of patients with vimentin‐positive IBC‐NSTs.…”
Section: Discussionmentioning
confidence: 50%
“…Since the values of average, median, minimum, and maximum of vimentin expression rates were almost similar between the 165 vimentin-positive IBC-NSTs and eight RNAanalyzed vimentin-positive IBC-NSTs, and the numbers of cases in each percentage category were almost similar between the two aforementioned groups of tumors, the RNA expression data obtained in this study most likely demonstrated the true characteristics of vimentin-positive IBC-NSTs. Among the top 10 lncRNAs found to be upregulated in vimentin-positive IBC-NSTs, although only LINC01694 and FAM74A7 have been reported previously as being significantly associated with a heightened malignant potential of carcinomas, 35,36 this study clearly demonstrated that the other eight lncRNAs could also be closely involved in accelerating the malignant potential of vimentinpositive IBC-NSTs; since there is as yet no published study report to suggest that these eight lncRNAs might also be closely associated with the outcome of carcinoma patients at the moment, these lncRNAs are most likely de novo lncRNAs accurately predicting the prognosis of patients with vimentin-positive IBC-NSTs.…”
Section: Mitotic Cytokinesismentioning
confidence: 99%
“…The ROC curves for the 7-year survival prediction were plotted with the timeROC R package ( Figure 9D ). The AUC values were 0.722 for our 3-gene ICI signature, 0.574 for the 7-gene Pan signature ( 32 ), 0.658 for the 6-gene Cheng signature ( 33 ), 0.644 for the 4-gene Wang signature ( 34 ), 0.696 for the 8-gene Liu signature ( 35 ), 0.806 for the 14-gene Li signature ( 36 ), 0.635 for the 8-gene Bi signature ( 37 ), 0.648 for the 5-gene Yu signature ( 38 ), and 0.623 for the 5-gene Hu signature ( 39 ) ( Figure 9D ). Although the AUC value ranks second, less than the 14-gene Wang signature, our ICI signature contains the least number of genes, which means it is more convenient for clinical applications.…”
Section: Resultsmentioning
confidence: 92%
“…As for OC, lncRNA-based prognostic signatures have been reported in previous investigations Pan and Bi, 2021). There are also lncRNA-based prognostic signatures for other cancers, such as breast cancer (Li et al, 2020b;Ma et al, 2020), glioma , bladder urothelial carcinoma (Sun et al, 2020), colorectal cancer (Sun et al, 2020;, esophageal cancer (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 89%